Coordinated approximation method for nonlinear ill-posed problems - Pham, Ky Anh. (Ukrains’kyi Matematychnyi Zhurnal, 1994)
A generalization of the method of coordinated approximation suggested by Yu. Gaponenko [1] for the space $L_2(0, 1)$ is developed for abstract Hilbeit spaces. In particular, it is shown that, for $L_2(0, 1)$,some assumptions concerning ал exact solution can be weaken.